HRM Strategies for Managing Generation Z Talent: Understanding Workplace Needs and Motivations - Indri Guslina; Rita Mardiana; Adrian Adha; Ahmad Juhari; Giharjo (Journal of Business and Management Inaba, 2025)
The purpose of this study is to examine the challenges and talent management strategies in managing Generation Z in the workplace. Generation Z, as digital natives, brings significant changes that demand the adaptation of an integrated Human Resource (HR) strategy. The method used is qualitative with a literature review approach, which collects data from various scientific journals, books, and research reports. The results of the study show that companies face challenges in three main aspects: attracting, employing, and retaining Generation Z. In terms of attracting, the challenges are building a strong company image and positive reputation, as well as creating an efficient and digital recruitment process. In terms of employing, the challenges are conducting holistic skill assessments (covering both soft skills and hard skills), implementing an effective and engaging onboarding process, and managing Generation Z's expectations realistically. Meanwhile, to retain Generation Z, companies must address the high turnover rate by providing a positive work environment, clear career development opportunities, and competitive compensation and benefit packages. By implementing these strategies, companies can not only maximize the potential of Generation Z but also be better prepared to face the challenges and opportunities of an increasingly digital future of work.